Teacher Strategies for Tactual Atlas-Based Social Studies Learning - Muchamad Ziran Albani; Iis Nurasiah; Rifky Aditya Ramadhan (JED (Jurnal Etika Demokrasi), 2026)
The urgency of this study arises from the persistent difficulty experienced by visually impaired students in accessing Social Studies content that is commonly presented through visual representations, particularly maps, regional forms, directional orientation, and spatial relationships. This study aims to analyze teacher strategies in implementing Tactual Atlas-based Social Studies instruction and to examine visually impaired students’ responses to the learning process. A qualitative case study was conducted at SLB-A Budi Nurani involving one fourth-grade teacher, two visually impaired students, and the school principal as a supporting informant. Data were collected through classroom observation, semi-structured interviews, and documentation of learning activities, instructional media, and field notes. The data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, conclusion drawing, and verification, while data credibility was strengthened through source triangulation, methodological triangulation, and member checking. The findings show that the teacher implemented adaptive, multisensory, and experiential learning strategies by integrating the Tactual Atlas with verbal explanations, audio media, guided tactile exploration, and concrete simulations. These strategies enabled students to understand geographical concepts more concretely, including landforms, regional boundaries, cardinal directions, geographical locations, and spatial relationships. Students responded positively to the use of the Tactual Atlas, although differences in comprehension and learning support needs were observed between students. This study concludes that Tactual Atlas-based instruction can enhance the accessibility and meaningfulness of Social Studies learning for visually impaired students. The novelty of this study lies in its analysis of teacher-mediated integration of the Tactual Atlas within actual classroom practice. The study contributes to inclusive education by offering practical insights for designing adaptive, multisensory, and accessible Social Studies instruction.